Responding to Sexual Harassment: Implications for Counselling Adolescent Girls - Luft, Toupey M.; Cairns, Kathleen V. (Canadian Journal of Counselling and Psychotherapy, 2007)
The purpose of this study was to outline the processes involved in adolescent girls' responding to sexual harassment. Grounded theory methodology was used to generate a theory of these processes. The core category elicited from interviews with ten participants was "learning about the self." Two processes were identified: "learning powerlessness" and "learning agency." These processes represented girls' movement from seeing themselves as "objects" of others' experience to becoming the "subjects" of their own experience. The counselling implications of the theory developed in the study are discussed.